Why Italians set their sights on East Africa? The developments and unfulfilled aspirations in the Mediterranean in the 19th century (Povijesni prilozi (Historical Contributions), 2020)
In the wake of the Unification the Italian expansionist designs were aimed, as expected, towards Africa. The fear of French aggression on the coast of North Africa drove Rome to the camp of the Central Powers, a diplomatic event of colossal importance for Europe's historical evolution until the First World War. The disturbance of the Mediterranean balance, when France occupied Tunisia and Britain Cyprus and Egypt, caused stress, anxiety and confusion among the statesmen of Italy, a fact which is reflected in their subsequent erroneous choices. The frustrations, the inability to find a colony in proximity to Italy's geographical area and the diplomatic defeats led Rome by inference to the Red Sea and Eritrea.